Measures of complexity in Nosé-Hoover oscillator and a possible new chaos generation mechanism - Deng, Bo (2023)
In this article, we undertake a study of the time-reversible dynamiics of the original Nosé-Hoover oscillator with the aim to identify its nontrivial chaos generating pathway. We examined the spectrum of Lyapunov exponent, predictability, and fractal dimension of both for- ward and backward chaotic attractors. We failed to identify any known chaos type that can explain our findings. We propose a new chaos generation mechanism that may be responsible for the enigmatic dynamics of the model.